2023
DOI: 10.1002/adhm.202203306
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Intrinsic Photothermal Hydrogel Bioadhesive with On‐Demand Removability for Wound Closure and MRSA‐Infected Wound Healing

Abstract: Photothermal hydrogel adhesives have yielded promising results for wound closure and infected wound treatment in recent years. However, photothermal hydrogel bioadhesives with on-demand removability without additional nanomaterials-based photothermal agents have rarely been reported in the literature. In this work, an injectable intrinsic photothermal hydrogel bioadhesive with an on-demand removal trait is developed through dynamic cross-linking of gelatin (Gel), tannic acid (TA) quinone, and borax for closing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…25 A recent report proposed incorporation of oxidized TA into gelatin solutions followed by cross-linking using borax (Figure 2A). 33 The hydrogels adhered to various tissue types (adhesion strength of up to ∼100 kPa), which improved further with increasing TA content (Figure 2B,C). Bioadhesion in these hydrogels was found to be pH-responsive, where increased acidity triggered hydrogel dissociation and aided in controllable deactivation of bioadhesion (Figure 2D).…”
Section: Physical Mixingmentioning
confidence: 92%
See 2 more Smart Citations
“…25 A recent report proposed incorporation of oxidized TA into gelatin solutions followed by cross-linking using borax (Figure 2A). 33 The hydrogels adhered to various tissue types (adhesion strength of up to ∼100 kPa), which improved further with increasing TA content (Figure 2B,C). Bioadhesion in these hydrogels was found to be pH-responsive, where increased acidity triggered hydrogel dissociation and aided in controllable deactivation of bioadhesion (Figure 2D).…”
Section: Physical Mixingmentioning
confidence: 92%
“…(D) Responsiveness of adhesion to pH. Reproduced with permission from ref . Copyright 2023 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Processing Methods For Incorporating Polyphenols In Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 153 ] It was demonstrated that NIR irradiation induced a highly effective antimicrobial activity in vitro and in vivo. [ 154 ]…”
Section: Antimicrobial Bioadhesive Design Requirementsmentioning
confidence: 99%
“…Fibrin glue, another common commercial bioadhesive, shows good biocompatibility and can maintain a soft wound, but its adhesive strength is low and often needs to be used with sutures . In addition, many underinvestigated hydrogel-based bioadhesives are potentially useful as alternatives. For example, Ke et al utilized natural macromolecular silk fibroin to spontaneously coassemble with a natural plant polyphenol, tannic acid, and iron oxide nanoparticles (Fe 3 O 4 NPs) to construct a silk fibroin-based bioadhesive. The produced bioadhesives are flexible, highly extensible, and self-healing, and they show considerable wet adhesion ability and biocompatibility .…”
Section: Introductionmentioning
confidence: 99%